CONDITION MONITORING OF INDUCTION MOTORS VIA INSTANTANEOUS POWER ANALYSIS - IRFAN, MUHAMMAD (2013)
Many techniques have been developed which support the construction of condition monitoring and fault diagnosis for induction motors. However, most of these techniques use sensors as theirintegral components which usually expensive and need to be properly installed on the machines for accurate results. Furthermore, sensors have some life period after which they may fail and in certain cases earlier than the bearings life period, which make these techniques unreliable. The idea for proposing instantaneous power analysis monitoring technique in this thesis comes from the usual practices in industries to have current and voltage transformers installed for the measurement of the current and voltage for control and display purposes.